Influence of the hardening treatment of a machine parts’ material on wear-resistance - Dudnikov, Anatolii; Dudnikov, Ihor; Kelemesh, Anton; Gorbenko, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2018)
Here we consider a task on improving resource of machinery and parts by employing more efficient technologies in mechanical engineering, both in the manufacture and repairing production at restoration. The main objective of present study is to substantiate and choose a more efficient method for increasing the durability and reliability of parts in piston assembly of internal combustion engines with respect to structural and materials-science factors. We have developed a technological process for the restoration of parts using a vibratory deformation whose special feature is the periodic action of a working body on the machined surface. We defined the following parameters for the technological process of vibratory hardening: deformation rate υ=0.030 m/s, machining tolerance A=2.0 mm, a working body is the punch with inclination angle β=11°, calibration belt height h=4 mm. The conditions and duration of the examined parts operation were analyzed, as well as methods for pretreatment, restoration techniques, and materials. An analysis of the factors that determine the wear intensity of parts’ working surfaces allowed us to develop a technological process of hardening both when manufacturing in mechanical engineering and while restoring in repairing production. We have investigated structural designs of a vibratory installation in order to choose higher efficiency of the technological process. The plasticity of parts increased by 21...27 % when using vibratory oscillations. The result of the conducted set of studies and experiments is the proposed technology for the restoration of bushings in connecting rods upper heads using a method of vibratory hardening. The essence and special features of the technology imply that a worn-out working layer is compensated for by a plastic vibratory deformation with a punch dispensing a nonworking layer. The use of a given technology makes it possible to obtain a surface with enhanced wear resistance. The results obtained in the course of present research could be used in machine building in order to harden the indicated parts during manufacturing.